2013
DOI: 10.1111/liv.12411
|View full text |Cite
|
Sign up to set email alerts
|

Variation in genes encoding for interferon λ‐3 and λ‐4 in the prediction of HCV‐1 treatment‐induced viral clearance

Abstract: In HCV-1 patients, the rs12979860 polymorphism appeared as the hit SNP better predicting response following peg-interferon and ribavirin treatment. Additional ss469415590 or rs8099917 genotyping had no added benefit for response prediction. In the subset of carriers of the rs12979860 T allele, genotyping of the rs8099917 SNP was unhelpful in the present investigation, but may inform clinical prediction of treatment response when our data were pooled with previous investigations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 17 publications
(55 reference statements)
0
10
0
Order By: Relevance
“…29 Additionally, five studies were conducted by the same group; 14,15,[30][31][32] therefore the most recent two were selected (Nagaoki 31 and Ochi 14 ); one of these provided detailed genotype information and one presented detailed allele frequencies. After excluding these 13 studies, the remaining seven articles were included in the meta-analysis, among which six articles investigated SVR, 6,[11][12][13]16,31 three articles investigated RVR, 13,16,31 one study investigated susceptibility, 14 and two studies explored spontaneous clearance. 6,11 These articles included a total 4480 HCV patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…29 Additionally, five studies were conducted by the same group; 14,15,[30][31][32] therefore the most recent two were selected (Nagaoki 31 and Ochi 14 ); one of these provided detailed genotype information and one presented detailed allele frequencies. After excluding these 13 studies, the remaining seven articles were included in the meta-analysis, among which six articles investigated SVR, 6,[11][12][13]16,31 three articles investigated RVR, 13,16,31 one study investigated susceptibility, 14 and two studies explored spontaneous clearance. 6,11 These articles included a total 4480 HCV patients.…”
Section: Resultsmentioning
confidence: 99%
“…[11][12][13] Meanwhile, the probability of achieving a virological response has varied in different ethnicities, and ss469415590 is more strongly correlated with HCV clearance than rs12979860. 6,12,14,15 However, one study reported contradicting results showing that IFNL4 ss469415590 had no added benefit for SVR prediction compared to rs12979860, 16 and another study reported IFNL4 ss469415590 to show similar predicting performance to IL28B rs12979860.…”
mentioning
confidence: 99%
“…We read the article by Palmieri et al with great interest. The study regarding the design, sample size and results is substantial (1). They evaluated the impact of single nucleotide polymorphisms (SNPs) of interferon lambda (IFNL) genes on hepatitis C treatmentinduced clearance in significant number of Caucasians as previously described as well (2,3).…”
Section: To the Editormentioning
confidence: 99%
“…They found that the rs12979860 C/C, rs8099917 T/T and ss469415590 TT/TT were significantly associated with sustained virological response (SVR). At univariate analysis, they found the IFNL SNPs to impact SVR with odds ratios (ORs) 5.15 and 4.73 for rs12979860 and ss469415590 respectively (1). They included the genetic variants into a multiple logistic model and subsequently concluded that the hit SNP was rs12979860 with OR 3.39, which was the one to retain an independent prediction power (1).…”
Section: To the Editormentioning
confidence: 99%
“…We thank Dr Keshvari and her collaborators (1) for their comments on our recently published paper on variations in IL28B locus in the prediction of HCV-1 treatment-induced viral clearance (2).…”
Section: Can We Include Genetic Variants With High Linkage Disequilibmentioning
confidence: 99%